Gozdnogospodarsko načrtovanje v Sloveniji po drugi svetovni vojni - Perko, Franc (Gozdarski vestnik, 2005)
The article presents the development of forest management planning in Sloveniaafter World War II. Its first beginnings and foundation are: the firstgeneral forest inventory (1946-47) and the second general forest inventory (1950-51) of all forest in Slovenia. Regular planning activities began in 1948, but were interrupted because of disordered circumstances. In 1952 regular planning proceeded in new, more favourable circumstances. The felling in forests was reduced, the forest service organization developed in the framework of forest management regions and forest management became decentralized. The prevailing method of determining growing stock became measurement of every tree and the increment was determined by drilling with increment borers. The study of forest sites was instituted. According to regulations (from 1953) the following plans began to be drafted in Slovenia for all forests: the long-term state forest management plan, plans for individual forest management regions and plans for individual forest management units.
Keywords: gozdarska politika; gozdno gospodarstvo; inventarizacija; Slovenija; zgodovinski pregledi